Object-oriented programming in C++ - Johnsonbaugh, Richard; Kalin, Martin (Upper Saddle River Prentice Hall, 2000)
A valuable handbook/reference for professionals who need to learn C++ and master its latest updates, this exceptionally organized, #1-rated guide teaches the power and flexibility of the C++ programming language through object-oriented programming applications. Examines the most up-to-date C++ features, including new-style headers, new-style casts, type bool, type string, stringstream classes, namespaces, namespace std., exception handling, run-time type identification, operator new , the template input/output classes, and more. Offers complete coverage on STL (standard template library), including containers, iterators, algorithms, and function objects; the standard input/output library IN DETAIL; and the Microsoft Foundation Classes. Contains an extensive number of well-constructed examples, beautifully fashioned sample applications, interesting and practical programming exercises, boxed figures and vibrant illustrations. A companion web site provides the book's source code, header files, and data files; sample syllabi; transparencies; and an errata list. For professionals in computer science and related fields.